Full-Length Trimeric Influenza Virus Hemagglutinin II Membrane Fusion Protein and Shorter Constructs Lacking the Fusion Peptide or Transmembrane Domain: Hyperthermostability of the Full-Length Protein and the Soluble Ectodomain and Fusion Peptide Make Significant Contributions to Fusion of Membrane Vesicles() - Ratnayake, Punsisi U. (Protein Expr Purif, 2015)
Influenza virus is a Class I enveloped virus which is initially endocytosed into a host respiratory epithelial cell. Subsequent reduction of the pH to the 5–6 range triggers a structural change of the viral hemagglutinin II (HA2) protein, fusion of the viral and endosomal membranes, and release of the viral nucleocapsid into the cytoplasm. HA2 contains fusion peptide (FP), soluble ectodomain (SE), transmembrane (TM), and intraviral domains with respective lengths of ~25, ~160, ~25, and ~10 residues. The present work provides a straightforward protocol for producing and purifying mg quantities of full-length HA2 from expression in bacteria. Biophysical and structural comparisons are made between full-length HA2 and shorter constructs including SHA2 ≡ SE, FHA2 ≡ FP + SE, and SHA2-TM ≡ SE + TM constructs. The constructs are helical in detergent at pH 7.4 and the dominant trimer species. The proteins are highly thermostable in decylmaltoside detergent with T(m) > 90 °C for HA2 with stabilization provided by the SE, FP, and TM domains. The proteins are likely in a trimer-of-hairpins structure, the final protein state during fusion. All constructs induce fusion of negatively-charged vesicles at pH 5.0 with much less fusion at pH 7.4. Attractive protein/vesicle electrostatics play a role in fusion, as the proteins are positively-charged at pH 5.0 and negatively-charged at pH 7.4 and the pH-dependence of fusion is reversed for positively-charged vesicles. Comparison of fusion between constructs supports significant contributions to fusion from the SE and the FP with little effect from the TM.